Medication Therapy Adherence Among Outpatient Patients With Hypertension - Dwi Amelia Nur Afifa; Adinugraha Amarullah (Jurnal Farmasi Ma Chung: Sains, Teknologi, dan Klinis Komunitas, 2026)
Hypertension is a chronic disease with an increasing prevalence and is a major risk factor for cardiovascular diseases such as stroke and kidney failure. One of the key components in hypertension management is patient adherence to medication therapy. Good medication adherence is essential to control blood pressure and prevent disease complications. This study aimed to determine the level of medication therapy adherence among patients with hypertension. This study employed a descriptive observational design with a cross sectional approach. Data were collected using purposive sampling by distributing the eight item Morisky Medication Adherence Scale questionnaire to 97 respondents. The results showed that most respondents had a moderate level of adherence, accounting for 41 respondents or 42.3 percent. This was followed by low adherence in 30 respondents or 30.9 percent, high adherence in 19 respondents or 19.6 percent, and the lowest adherence category was non adherence, found in 7 respondents or 7.2 percent. Moderate to low adherence was mainly caused by patients forgetting to take medication or not taking it on time, discontinuing treatment when they felt healthy without consulting a physician, and stopping medication due to perceived side effects after drug consumption. In conclusion, medication adherence among patients with hypertension remains suboptimal and requires improved patient education and continuous monitoring to enhance treatment outcomes.